2005
DOI: 10.1242/jeb.01826
|View full text |Cite
|
Sign up to set email alerts
|

Effects of decreased muscle activity on developing axial musculature innicb107mutant zebrafish (Danio rerio)

Abstract: SUMMARY The present paper discusses the effects of decreased muscle activity (DMA)on embryonic development in the zebrafish. Wild-type zebrafish embryos become mobile around 18 h post-fertilisation, long before the axial musculature is fully differentiated. As a model for DMA, the nicb107mutant was used. In nicb107 mutant embryos, muscle fibres are mechanically intact and able to contract, but neuronal signalling is defective and the fibres are not activated, rendering the embryos immobile. Desp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 64 publications
4
10
0
Order By: Relevance
“…They were approximately the same size as the sop mutants and nicotine-exposed wild-type larvae. We conclude that the size reduction reported in this paper may not be related to muscle degeneration or abnormal axonal pathfinding, but may simply be an effect of prolonged paralysis consistent with observations of van der Muelen et al, 2005.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…They were approximately the same size as the sop mutants and nicotine-exposed wild-type larvae. We conclude that the size reduction reported in this paper may not be related to muscle degeneration or abnormal axonal pathfinding, but may simply be an effect of prolonged paralysis consistent with observations of van der Muelen et al, 2005.…”
Section: Discussionsupporting
confidence: 85%
“…or wild-type larvae. This size reduction has been reported by another group studying the nic1 mutant zebrafish (van der Muelen et al, 2005), and is not likely related to axonal pathfinding errors or degenerated muscle because in the sop mutants, muscle and motoneuron axons are present and appear normal (our work and Ono et al, 2001). In nicotine-exposed wild-type larvae, the motoneuron axons and muscle are altered.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Pseudohelical muscle fibre arrangements are generated despite the immobility ( Van der Meulen et al, 2005). Although the initial development of curved muscle fibre trajectories does not depend on active muscle, the architectural fine tuning in later stages (2·d.p.f.…”
Section: Effects Of Immobility On Muscle-fibre Arrangementmentioning
confidence: 99%
“…For example, muscle contractions could stimulate stretch-activated channels on the muscles or the skin, which in turn could alter secretion or regulate localization of an extracellular guidance molecule expressed in a dorsal-ventral gradient. Interestingly, the mRNA expression of collagen 1α2 in the skin is altered in the chrna1 (nic-1) mutant (van der Meulen et al, 2005), although it is unknown if collagen 1α2 affects peripheral RB axon direction. We also found that CSPG expression is reduced in chrna1 (nic-1) mutants, suggesting that muscle activity can somehow affect CSPG levels.…”
Section: Discussionmentioning
confidence: 99%